Optimizing Electrical Efficiency and Thermal Performance of AMD Ryzen 3 2200G Processor through Undervolting in Synthetic Benchmarks and Gaming Scenarios - Rizqi Sukma Kharisma; Ibnu Herlambang Wicaksono (Advance Sustainable Science Engineering and Technology, 2023)
Undervolt is a term that refers to a way to make a computer device run on lower electrical power than the manufacturer's provisions. To do undervolting requires a good experience for user and computer devices that are good or specialized for undervolt purposes such as processors. This study aims to find the optimal minimum voltage that the processor can use without causing performance degradation or instability, and temperature drops that the processor produces while it is running. In this study, the author tested a processor device with the type of AMD Ryzen that already supports the undervolting process from the factory. AMD Ryzen 3 2200G processor is one of the processors with 14nm fabrication, where this processor promises significant performance with the number of cores, memory chace capacity, and power efficiency. On this day, many games demand the use of an aggressive processor. Of course, this will consume power on a larger processor. The author conducted several test scenarios to get the best performance. It was found that the scenario with undervolt at 1.25V showed the best performance.